Hydro-edaphic Properties of Woodland Habitat of Nilgiris Biosphere Reserve-kerela and their Relationship with its Flora-Part-II - Singh, J. N.; Chaturvedi, S. P. (Indian Forester, 2011)
The present study was aimed at to investigate the hydro-edaphic properties of Woodland habitat of Nilgiris Biosphere Reserve (NBR)-Kerela and their possible relationship with its flora. Results revealed that hydro-edaphic properties of NBR Kerela are divergent in nature and, together, they are capable to hold the vegetation of the region in present form. NBR- Kerala- portion is only core area, which possesses the elements of rain-forest. Mechanically, the soils within NBR- Kerala are quite sound and capable to support the taxa of mighty dimension and lofty height. There are seven textural classes of soils. Data on physico-chemical characteristics of the soil of NBR - Kerela demonstrate the superiority of their acquired characteristics over inherent. It is further illustrated that one delicate but stable equilibrium is functioning among soil-vegetation and climate of the region, which is intact in Kerala - NBR. Soils as whole are feebly acidic to moderately acidic in reaction, possess sufficient reserve of energy materials. Their other physico-chemical characteristics such as water holding capacity, porosity, available nitrogen, phosphorus and cation exchange capacity are relatively superior. The water regimes of NBR- Kerela are divergent in their chemical characteristics / composition. It is categorized as C1 S1 class and as such have direct bearing on flora and fauna of the area. It is finally concluded that soil’s physico-mechanical characteristics along with water availability are more responsible for floristic diversity than their chemical characteristics within biosphere reserve.